Fabrication of Functional Materials for Dye-sensitized Solar Cells - Tontapha, Sarawut; Uppachai, Pikaned; Amornkitbamrung, Vittaya (Frontiers in Energy Research, 2021)
Dye-sensitized solar cells (DSSCs) have been developed as a promising photovoltaic cell type in recent decades because of their low cost, environmental friendliness, ease of fabrication, and suitability for a wide range of indoor and outdoor applications, especially under diverse shaded and low-light condition. They are typically composed of three main components: a transparent conducting oxide (TCO) substrate-based working electrode with wide-bandgap semiconductors and dye sensitizer molecules, an electrolytic mediator based on redox couple species, and a TCO-based counter electrode consisting of catalyst materials. The development of intrinsic and functional organic, inorganic, metal oxide, composite, and carbon-based materials has been intensively studied to enhance the efficiency of DSSCs. A simple and low-cost fabrication process that uses natural products is also considered essential for further large-scale production. In this article, we review the fabrication of various functional materials and their effects on DSSC performance.